Multi-wavelength selection and identification of gamma-ray blazar candidates. Issue Volume 10:Issue S313(2014) (24th March 2015) - Paggi, Alessandro; D'Abrusco, R.; Massaro, F.; Landoni, M.; Milisavljevic, D.; Masetti, N.; Ricci, F.; Jiménez-Bailón, E.; Chavushyan, V.; Giroletti, M.; Smith, H. A.; Margutti, R.; et al.
Abstract: A significant fraction (~ 30%) of the gamma-ray sources detected by the Fermi Gamma-ray Space Telescope is still of unknown origin, being not yet associated with counterparts at lower energies. Many unidentified gamma-ray sources (UGSs) could be blazars, the largest identified population of extragalactic gamma-ray sources and the rarest class of active galactic nuclei. In particular, it has been found that blazars occupy a defined region in WISE three dimensional color space, well separated from that occupied by other sources in which thermal emission prevails. For farther sources with weaker IR emission, additional informations can be obtained combining WISE data with X-ray or radio emission. Alternatively, the low-frequency radio emission can be used for identifying potential gamma-ray candidate blazars. However, optical spectroscopic observations represent the tell-tale tool to confirm the exact nature of these sources. To this end, an extensive observational campaign has been performed with several optical telescopes, aimed at pinpointing the exact nature of gamma-ray candidate blazars selected with the different selection methods mentioned above. The results of this campaign lead to the discovery of 60 new gamma-ray blazars, thus confirming the effectiveness of these selection criteria.